Integrated Analysis of Optimizing Tubing Material Selection for Gas Wells - Bonar Tua Halomoan Marbun; Samuel Zulkhifly Sinaga; Calvin Lumban Gaol; Gde Valdy Irawan Arimbawa; Aristya Putra Pamungkas; Aldiano Falah Hardama; Ricko Rizkiaputra (Journal of Engineering and Technological Sciences, 2015)
Corrosion in production tubing strings is seen as a challenging problem in gas wells containing carbon dioxideand hydrogen sulfide. This paper presents a new comprehensive method of corrosion rate calculation with integrated study of reservoir condition, nodal analysis of the well, and well trajectory, which could also have an effect due to the possibility of different flow regimes of the production fluid. This method  is applicable to evaluate and predict the performance of selected tubing size and material. This method can also give an economic evaluation for the consideration of using corrosion resistant alloy (CRA) or low-alloy steel and carbon steel. The measurement of corrosion rate can be done by several methods,such as using corrosion coupons, calculating the iron content inside  the production fluid, or probes. Either way, when  the corrosion rate measured in the field is still below the acceptable maximum corrosion rate, it can be said that the adequacy of this method is guaranteed. This method has been implemented in a gas field,where it successfully selected the best tubing material for the next development well in this field. Consequently, the lifetime of the tubing strings could be extended,resulting in an economical benefit as well.